Perlindungan Hukum Terhadap Hak-Hak Konsumen Yang Membeli Produk Makanan Kadaluwarsa - Rahwindi Pangestu Nugroho Putri; Sri Wahyuni; Rabiah Aldawiah (Jurnal Hukum Sasana, 2022)
The 1945 Constitution of the Republic of Indonesia in article 1 paragraph (3) states that "the State of Indonesia is a state of law", meaning that all citizens and law enforcement officers must comply with applicable laws. In the current era of globalization and trade, various products are marketed to consumers in supermarkets, advertising promotions and direct offers. the facts that consumers in the community are still many who are harmed by producers or business actors such as food products that have expired are sold to consumers. So with the existence of business actors who sell expired food products so that they can harm consumers' rights to comfort, security, safety in consuming goods and services as well as harm from the health aspect. This study aims to examine a legal protection against consumer rights and compensation to consumers and to find out the responsibilities of business actors who sell expired food products. The type of research used in this research is normative law by using primary and secondary data. The approach used is a statutory approach and a case approach.